Effect of dietary inulin with hypercholesterolemia - amer, saraa; Sadiq Jaafir Aziz Alneamah, Sadiq Jaafir Aziz Alneamah (University of Thi-Qar Journal of agricultural research, 2025)
The carbohydrates known as non-digestible oligosaccharides (NDO) include inulin-fructooligosaccharides (FOS), which have been consumed by humans for a very long time. In vitro and in vivo research have demonstrated that inulin has several nutritional benefits, primarily related to the stimulation of bifidobacteria. Similar to dietary fiber, inulin shares all the properties and health advantages of non-digestible polysaccharides (NDP). The normal physical effects of dietary fiber, including significant increases in osmotic pressure, intestinal bulking effects, intensive water holding, and dramatic viscosity building, are not present in inulin.The capacity of inulin to specifically promote the growth of bacterial genera and species known to be health-promoting in vivo in humans, such as Bifidobacterium (apart from Bifidum) and Lactobacillus, at the expense of potentially harmful microorganisms, accounts for a number of the vitamin's more notable health benefits. Therefore, inulin is typically regarded as a bifidogenic factor prebiotic. Prebiotics, such as inulin, have the advantage of promoting the selective growth of endogenous bacteria in their natural habitat, without being overly impacted by their surroundings, unlike probiotics.Inulin can be referred to as a "physiologically functional food" or food ingredient, or simply a food with potential health-promoting effects, due to its effects on gut microbiota, blood glucose attenuation, lipid homeostasis, mineral and nitrogen bioavailability, immunomodulation effects, and the ability to add texture and improve rheological characteristics and nutritional properties of food.